“Clean smoke”: solusi inovatif dan efektif untuk mengurangi emisi gas karbon dan partikulat berbahaya pada asap - Mahmud, Muhammad Khairul; Izza, Fadel; Juniar, Nadya Fildzah; Alqauliyah, Alqauliyah; Syam, Alif Rahmawan; Sjafruddin, Rahmiah (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
Many environmental problems currently faced globally are related to air pollution, primarly originating from biomass combustion on both small or large scales. Major contributors to particulate matter (PM2.5) and harmful organic substances such as CO can be found in the smoke from the combustion process. These particulates and toxic substances have been known to have adverse effects on human health. This study presents the design and development of a device called Clean Smoke, which has an efficiency rate of 78.65% in reducing harmful substances in air emissions and effectively trapping organic compounds from biomass. In addition, the test results showed that the residual waste liquid or liquid smoke produced by this tool showed a significant turbidity increase from 4.16 NTU to 25.5 NTU, indicating the ability of the tool and activated carbon to bind hazardous particulates in water. With further development, Clean Smoke device could significantly reduce exposure to emissions and toxic substances from combustion processes in small to large-scale industries, thereby contributing to a healthier environment and supporting the global goal of achieving zero-net emissions.